An Analysis of the Influencing Factors in the Establishment of the Overseas Agricultural Cooperation Zones under the Belt and Road Initiative Based on Logit Model. (29th December 2021) - Zheng, Huiqing; Zhuang, Peifen
Abstract : A total of 57 overseas agricultural cooperation zones have been selected from 68 countries along the Belt and Road and extended areas from 2006 to 2018 as samples, and the corresponding indexes of bilateral trade in agricultural products, agricultural resource endowments, labor resources, infrastructure, and economic freedom have been chosen for parameter estimation based on the maximum likelihood method under the Logit model for an empirical analysis of the main influencing factors in the establishment of the overseas agricultural cooperation zones. The empirical analysis results indicate that the total import and export trade volume of agricultural products, agricultural land area, and labor resources of the host country have a significant promoting effect on the establishment of overseas agricultural cooperation zones. The economic freedom index has a significant negative impact on the establishment of overseas agricultural cooperation zones, while the port throughput has no significant impact. China should consider several main factors when selecting a host country to establish overseas agricultural cooperation zones, including bilateral trade volume of agricultural products, agricultural resource endowments, labor resources, and economic freedom of the host country, which can provide reference for the spatial layout of the overseas agricultural cooperation zones.